(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to explore the relationship between excessive use of social media applications and digital social isolation. Through this general objective, the following sub-objectives will be identified: To determine the patterns of social media application use. To highlight the impact of digital social isolation on social relationships and real social interaction. To reveal the reasons behind excessive use of social media applications. This study falls under the category of descriptive-analytical studies. The sample consisted of female students from the College of Education in Az Zawiyah / University of Zawiya, selected randomly, totaling 134 students for the academic year 2024-2025. The study yielded several findings, most notably: Excessive use of social media contributes to a decline in direct interaction, enhances reliance on the digital environment, which leads to shallower and less impactful relationships, increases feelings of loneliness, reduces active social participation, and reinforces the idea that dependence on digital media may cause psychological and social harm, altering traditional relationship patterns. Weak direct interaction and increased reliance on virtual interaction lead to weaker social relationships. The study confirms that the digital interaction environment diminishes individuals’ ability to build deep and mutual social meanings, which affects the quality and nature of social relationships.